The ABCs of writing motivation: a systematic review of factors emerging from K–5 students’ self-reports as influencing their motivation to write - Alves-Wold, Aline; Walgermo, Bente Rigmor; McTigue, Erin; Uppstad, Per Henning (Frontiers in Education, 2024)
Motivation is essential for writing success. However, investigations of writing motivation in younger students often overlook the students' voices, basing instead-insufficientlyfindings solely on teachers' and/or researchers' observations. The present systematic literature review highlights the importance of also listening to students' own perspectives. It synthesizes findings from empirical studies in K-5 classrooms. Of 5795 studies initially identified, 56 met the inclusion criteria and were qualitatively analyzed. The analysis yielded nine factors that influence writing motivation. They are presented as the ABCs of Writing Motivation, organized according to the first nine letters of the alphabet: (A) Appeal, (B) Beliefs, (C) Choice, (D) Difficulty, (E) Environment, (F) Feedback, (G) Goals, (H) Help, and(I) Instructor. We suggest that this can be a useful tool both for researchers and for teachers, as a checklist or source of ideas when planning writing lessons or interventions.